Numerical study of the combustion and application of SNCR for NOx reduction in a lab-scale biomass boiler. (1st June 2021) - Mousavi, Seyed Morteza; Fatehi, Hesameddin; Bai, Xue-Song
Highlights: CFD simulation of a lab-scale biomass boiler is presented with detailed chemistry. Multiple tar species are considered to avoid using the global reaction schemes. Application of selective non-catalytic reduction with ammonia is studied. Effects of ammonia injection height and flow rate on NO reduction is investigated. Abstract: In this paper, a numerical study of flow, reactions and NO x emissions from a biomass boiler is presented. Detailed reaction mechanisms for the decomposition of tar species, combustion of hydrocarbons and formation of NO x are employed by adopting appropriate reaction sets from literature. The proposed mechanism is used to perform CFD simulations of a laboratory-scale biomass boiler, and temperature and species concentrations are compared with the experimental data. NO x formation and emissions are studied in detail and the contribution of different pathways for NO x formation are identified. Furthermore, the CFD model is used to study the application of Selective Non-Catalytic Reduction (SNCR) method in this boiler. The effects of height and flow rate of ammonia injection on the performance of SNCR method are studied. It is observed that the SNCR, can reduce up to 63% of NO x emissions.